An Unknown Copy of Dîvân-ı Hikmet and New Wisdoms in it / Dîvân-ı Hikmet’in Bilinmeyen Bir Yazmasında Bulunan Yeni Hikmetler - Mehdi Rezaei (Folklor/Edebiyat, 2021)
Ahmad Yasawi is one of the poets who had a powerful influence on Turkic culture and literature. Yasawi, for centuries, has been a source of inspiration for many poets in Turkic lands and has played a pioneering role in Sufi poetry. Until today, different copies of Dīvān-i Ḥikmet have been found, based on which different editions of the work have been published. Although in historical sources such as Mihmannâmeyi Buhara it has been mentioned as the old copies of Dīvān-i Ḥikmet, the copies we have are mostly copied in the nineteenth century. These copies which differ from each other, generally contain wisdoms from other poets. This paper has dealt with a new copy of Dīvān-i Ḥikmet in The National Library of Iran. Moreover, descriptions are provided on the features of this copy and compared with published copies, where is necessary. There are differences between this 190-page copy and the copies that have been published so far. It contains new wisdoms that does not exist in other copies. There are, in this copy, in addition to ten wisdoms in which the pen name of other poets are seen, 60 other wisdom and one litany. Sixteen of the 60 wisdoms are new. This new wisdom, which includes nearly 370 verses, will undoubtedly give a new identity to Dīvān-i Ḥikmet.